Harmonic-Rejection Compact Bandpass Filter Using Defected Ground Structure for GPS Application. (3rd April 2014) - Liu, Haiwen; Ren, Baoping; Xiao, Xiang; Zhang, Zhichong; Li, Shen; Peng, Suping
Abstract : A miniaturized bandpass filter (BPF) using defected ground structure (DGS) resonator with the characteristic of harmonic rejection is developed in this paper. The second and third harmonics of the proposed BPF are rejected by the characteristic of stepped-impedance DGS resonator. Moreover, open stubs are established so that two adjustable transmission zeros can independently be created to extend the stopband and improve the rejection level. Finally, a second-order BPF, centered at 1.62 GHz with a stopband extended up to 5.6 GHz and a rejection level better than 20 dB, is designed and implemented for GPS application. A good agreement between simulation and measurement verifies the validity of this design methodology.